Why Did Nasdaq Market Makers Stop Avoiding Odd-Eighth Quotes? - Christie, William G; Harris, Jeffrey H; Schultz, Paul H (Journal of Finance, 1994)
On May 26 and 27, 1994, several national newspapers reported the findings of W. Christie and P. Schultz (1994) who cannot reject the hypothesis that marketmakers of active NASDAQ stocks implicitly colluded to maintain spreads of at least $0.25 by avoiding odd-eighth quotes. On May 27, dealers in Amgen, Cisco Systems, and Microsoft sharply increased their use of odd-eighth quotes, and mean inside and effective spreads fell nearly 50 percent. This pattern was repeated for Apple Computer the following trading day. Using individual dealer quotes for Apple and Microsoft, the authors find that virtually all dealers moved in unison to adopt odd-eighth quotes.